Chromosome Level Assembly of Homozygous Inbred Line ‘Wongyo 3115’ Facilitates the Construction of a High-Density Linkage Map and Identification of QTLs Associated With Fruit Firmness in Octoploid Strawberry (Fragaria × ananassa) - Lee, Hye-Eun; Manivannan, Abinaya; Lee, Sun Yi; Han, Koeun; Yeum, Jun-Geol; Jo, Jinkwan; Kim, Jinhee; Rho, Il Rae; Lee, Ye-Rin; Lee, Eun Su; Kang, Byoung-Cheorl; Kim, Do-Sun (Frontiers in Plant Science, 2021)
Strawberry is an allo-octoploid crop with high genome heterozygosity and complexity which hinders the sequencing and assembly of the genome. However, in the present study we have generated a chromosome level assembly of octoploid strawberry sourced from a highly homozygous inbred line ‘Wongyo 3115’ using long and short-read sequencing technologies. The assembly of 'Wongyo 3115' produced 805.6 Mb of the genome with 323 contigs scaffolded into 208 scaffolds with an N50 of 27.3 Mb after further gap filling. The whole genome annotation resulted in 151,892 genes with a gene density of 188.52 (genes/Mb) and validation of genome using BUSCO analysis resulted in 94.10% complete BUSCOs. Firmness is one of the vital traits in strawberry which facilitate the postharvest shelf life qualities. The molecular and genetic mechanisms that contribute the firmness in strawberry remains unclear. We have constructed a high-density genetic map based on the ‘Wongyo 3115’ reference genome to identify loci associated with firmness in the present study. For the QTL identification, ‘BS F2’ population developed from two inbred lines were genotyped using Axiom 35K strawberry chip and marker positions were analyzed based on the ‘Wongyo 3115’ genome. High-density genetic maps were constructed with 2,697 bin markers spanning the 4,961 cM. Using firmness data of ‘BS F2’ obtained from two consecutive years, five QTLs were identified on chromosomes 3-1, 3-4, 6-4, and 7-1. Further, we predicted the candidate genes associated with firmness in strawberries by utilizing transcriptome data and QTL information. Overall, we present the chromosome-level assembly and annotation of homozygous octoploid strawberry inbred line available to date and high-density linkage map constructed to identify QTLs associated with fruit firmness.